Asthma is associated with a lower incidence of metastatic colorectal cancer in a US patient cohort - Beckstead, Jacob; Mehrotra, Kunaal; Wilson, Kayla; Fingleton, Barbara (Frontiers in Oncology, 2023)
In previous pre-clinical studies, we examined the contribution of interleukin 4 receptor (IL4R) signaling in the progression and metastasis of colorectal cancer (CRC). Aberrant activation of this receptor can result in atopic diseases such as asthma. We hypothesized that further evidence for the contribution of excessive IL4R being associated with CRC progression could be seen in medical records, and specifically that chronic asthma patients were more likely to be diagnosed with metastatic CRC. To test this hypothesis, we took advantage of the Synthetic Derivative, a resource developed at Vanderbilt University Medical Center that hosts de-identified data taken from the electronic medical record. We developed search protocols that produced retrospective cohorts of invasive CRC patients and cancer-free equivalents. In comparing 787 metastatic CRC patients to 238 non-metastatic patients, we actually found significantly fewer asthmatics went on to develop metastatic CRC (P=0.0381). By comparing these groups together against 1197 cancer-free patients, even fewer asthmatic patients would develop invasive CRC (P<0.0001). While these results are clearly in opposition to our original hypothesis, they still support a link between chronic asthma and metastatic CRC development. One intriguing possibility, that will be examined in the future, is whether treatment for chronic asthma may be responsible for the reduction in metastatic cancer.